Efeitos da dieta de cafeteria na gestação sobre as respostas comportamentais em camundongos durante lactação e a repercussão nos filhotes adolescentes - Ribeiro, Ana Cláudia Alves Freire (2016)
During pregnancy and lactation occur several physiological, hormonal and psychological changes that can alter the maternal behavior (MB) for the development of their young. During this period, adequate and balanced nutrition plays an important role, since fetal nutrition is linked with the dietary intake of the mother and maternal nutrient stocks, so a balanced diet is a protective factor for offspring and the mother. So our objective was to evaluate the influence of cafeteria diet (CD) in the MB of lactating mice, since this diet is similar human and has high calorie content. The experiment was approved by the local ethics committee and consisted of two groups: normal diet (ND) and CD. Behavioral responses were evaluated Lee index, and abdominal fat on mothers treated with the following diets during pregnancy. And in the offspring were evaluated tests in light and dark, forced swimming, open field e play behavior, Lee index, abdominal fat, and physical developments and reflections. Based on the results it is concluded that mothers treated with CD MB have more pronounced when compared to ND, increased Lee index and abdominal fat, besides presenting a reduction in predictive anxiety behavior and reduced mobility. Regarding juvenile offspring noted an increase in predictive anxiety behavior and Lee index, of mother who consumed CD compared to ND. And in females a reduction in play behavior. And both sexes increased by abdominal fat, a delay in the physical developments and reflections and decreased play behavior. Therefore, it can be concluded that the CD has changed not only the MB but that inadequate nutrition in early life interfere with the behavior and development of offspring.